Al-Qasas dan Al-Amsal dalam Q.S. Al-Kahfi: (Studi Tafsir Maqasidi Perspektif Ibn ‘Asyur dan Al-Maragi) - Rifa'atul Mahmudah Emha; M. Ziyad Ulhaq; Muhammad Ulinnuha (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
Al-Qasas and al-amsal have not yet received a large portion of exploration from the maqasid side, even though their percentage in the Al-Quran is very large. Research on maqasid Al-Quran has begun to be carried out a lot, but existing research focuses on maqasid figures or discussion of maqasid Al-Quran with an asy-shariah maqasid perspective. Therefore the author tries to conduct research on the theme of Al-Qasas and al-amsal in Surah Al-Kahf with the aim of elaborating the interpretation of the verses that are the object of research using the Maqasidi Tafsir approach and contextualizing them. In this study the authors conducted a library research (library research) with the primary data source of Tafsir At-Tahrir wa At-Tanwir and Tafsir Al-Maragi by conducting data analysis using the Wasfi Asyur methodology.The results of this study indicate that between maqasid tafsiliyyah Al-Qasas and al-amsal in Q.S. Al-Kahf is tatsbit wa taqwiyah al-Iman (confirms and strengthens faith), hifzad-din (guarding religion), at-ta'yid (strengthening), at-tazkir (remembrance). The application of the maqasidi method boils down to the contextualization of the verses under study. Among the results: verbal bullying of preachers in cyberspace as a result of the study of maqsad taqwiyah al-Iman: critical thinking and the urgency of forecasting science in making policies based on the results of the study of maqsad al-i'tibar: Technological innovation as a means of national defense as a result of reading maqsad hifzan-nafs and hifzal-mal.